Video mapping and geographical information system synchronization for road asset management - Leong, Wai Sing, 1985-, author; Mohd. Safie Mohd, supervisor; Fakulti Geoinformasi dan Harta Tanah (2010)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2010